2021
DOI: 10.3233/faia210415
|View full text |Cite
|
Sign up to set email alerts
|

Optical Vortices Sharp Focusing by Silicon Ring Gratings Using High-Performance Computer Systems

Abstract: The diffraction of vortex laser beams with circular polarization (with different direction of polarization rotation) by silicon ring gratings was investigated in this paper. The silicon diffractive axicons with different numerical apertures (NA) were considered as such ring gratings. The considered diffractive axicons are compared with single silicon circular protrusion (cylinder). The finite difference time domain method was used for Light propagation (3D) through the proposed silicon ring gratings and silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that under certain conditions, a conventional round protrusion can be used to recognize polarization and focusing, and the focusing will be better than for a diffractive axicon with a similar grating size 32,43 . But the relief height also plays a key role 44,45 .…”
Section: The Investigation Laguerre-supergauss (10) Modes Diffraction...mentioning
confidence: 99%
“…Previous studies have shown that under certain conditions, a conventional round protrusion can be used to recognize polarization and focusing, and the focusing will be better than for a diffractive axicon with a similar grating size 32,43 . But the relief height also plays a key role 44,45 .…”
Section: The Investigation Laguerre-supergauss (10) Modes Diffraction...mentioning
confidence: 99%
“…The numerical calculations (3D) of the laser radiation propagation were performed using the finite difference time domain method (FDTD) using high-performance computer systems in the Meep software package [69][70][71][72] . The calculations were carried out on a computing cluster with a capacity of 850 Gflop.…”
Section: Introductionmentioning
confidence: 99%
“…Diffraction optics are often used to form vortex beams [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76], including multi-order diffractive optical elements [65][66][67], spiral phase plates [68][69][70], spiral and twisted axicons [71][72][73], and elements with a complex surface shape [73,74]. It is known that one can use spiral phase microplates manufactured at the end of a waveguide to form vortex beams in optical connector systems in data centers [76].…”
Section: Introductionmentioning
confidence: 99%